Protection Of Patent Rights (Comparative Studies in Japan and Indonesia (Faculty of Law, Universitas Negeri Semarang, 2019)
difference is motivated by the legal system used. Japan uses a common law and Indonesian system that uses the civil law system even though finally Indonesia finally mixes both of them, but the determination of the civil law used in Indonesia is still very thick. This article discusses an Indonesian young man who has had 14 patents in Japan because of his intelligence in creating patent works in Japan, namely the country he has occupied since college until now working in a leading company in Japan. The results of the study show that Japan, which legally adheres to the United States with common law, but in terms of Japanese patent protection adheres to the civil law system as used in Indonesia. The method used is normative juridical data collection techniques carried out by way of viewing or studying documents / libraries (library research).